P190 Complement system genes mutation spectrum in russian children with atypical hemolytic uremic syndrome. (6th June 2017) - Tsygin, Alexey; Ananin, Petr; Mazo, Alexandra; Komarova, Olga; Vashurina, Tatiana; Zrobok, Olga; Pushkov, Alexander; Savostianov, Kirill
Abstract : Background: atypical hemolytic-uremic syndrome (aHUS) is a rare, mostly genetic disease caused by complement system disorder. In contrast with classic post diarreal HUS it has a severe, often relapsing course with an outcome into end stage renal disease. There is a variable mutation spectrum reported worldwide. The efficacy of the only approved medication- Eculizumab needs a further study to build up a proper approach. Aim of the study: to investigate the prevalence of complement system genes mutations in Russian children with aHUS, to study a genotype to phenotype correlations, to evaluate the efficacy of Eculizumab treatment. Methods: We investigated CFH, CFI, CFB, MCP and THBD genes mutations by new generation sequencing and CFHR1/CFHR3 deletions by MPLA technique. The cases reports of children with aHUS were analysed to find a possible relation of clinical and laboratory data during the onset and follow up to genetic data and Eculizumab efficacy. Results: Seventy one child (31 male and 40 female) aged 6 months to 17 years with aHUS were investigated. In 46, 5% the mutations in CFH (12, 7%), CFI (1, 4%), CFB (11, 3%), MCP (8, 5%), THBD (1, 4%) u CFHR1/CFHR3 (16, 9%) genes were found. Another 7% had rare polymorphisms in these genes. We did not find any differences in clinical data at the onset. The only significant difference at the follow up was a more frequent relapses in mutation carriers. Eculizumab was efficient even if started later than 6 months after the onset allowing to stop dialysis in most (15 of 18) of the patients while all without Eculizumab had to continue dialysis. After at least one year of treatment Eculizumab was successfully discontinued in five children without mutation whose condition was stabilised and renal function restored. All 4 mutation carriers relapsed after Eculizumab discontinuation. Conclusion: The prevalence of gene mutations in Russian children with aHUS is compatible with worldwide data. The genetic data may help to predict a disease course and duration of Eculizumab treatment.